Small Cell Carcinoma of the Lung Presented as Acute Pancreatitis. Case Report and Review of the Literature - Hussain, Abdulzahra; Adnan, Ali; EL-Hasani, Shamsi (JOP. Journal of the Pancreas, 2012)
Context Small cell carcinoma of the lung is an aggressive cancer with gloomy prognosis. Links to acute pancreatitis is extremely rare. Case report We are reporting a 53-year-old patient who was admitted because of acute pancreatitis. She had no history of gallstones, alcohol abuse, medications or any other predisposition for acute pancreatitis. Further investigations of blood, CT of chest abdomen and neck and ultrasound scan of abdomen, bone marrow and neck lymph node biopsies confirmed advanced small cell carcinoma of the lung with hypercalcemia, which was the only definite cause of acute pancreatitis. The patient made good recovery from pancreatitis after controlling the hypercalcemia. She was referred to respiratory team for further management of lung cancer. Conclusion Acute pancreatitis due to hypercalcemia of advanced small cell carcinoma of the lung is an extremely rare condition. Acute pancreatitis due to hypercalcemia should be thoroughly investigated to exclude serious pathology as in our case. Image: Chest X-ray showing mediastinal mass.